Stem cell characteristics in glioblastoma are maintained by the ecto-nucleotidase E-NPP1 - Bageritz, Josephine; Puccio, L.; Piro, Rosario M.; Hovestadt, Volker; Phillips, Emma; Pankert, Teresa; Lohr, Jennifer; Herold-Mende, Christel; Lichter, Peter; Goidts, Violaine (Cell death and differentiation, 2014)
Glioblastomas are highly aggressive brain tumours and are characterised by substantial cellular heterogeneity within a single tumour. A sub-population of glioblastoma stem-like cells (GSCs) that shares properties with neural precursor cells has been described, exhibiting resistance to therapy and therefore being considered responsible for the high recurrence rate in glioblastoma. To elucidate the underlying cellular processes we investigated the role of phosphatases in the GSC phenotype, using an in vitro phosphatome-wide RNA interference screen. We identified a set of genes, the knockdown of which induces a significant decrease in the glioma stem cell marker CD133, indicating a role in the glioblastoma stem-like phenotype. Among these genes, the ecto-nucleotidase ENPP1 (ectonucleotide pyrophosphatase/phosphodiesterase 1) was found to be highly expressed in GSCs compared with normal brain and neural stem cells. Knockdown of ENPP1 in cultured GSCs resulted in an overall downregulation of stem cell-associated genes, induction of differentiation into astrocytic cell lineage, impairment of sphere formation, in addition to increased cell death, accumulation of cells in G1/G0 cell cycle phase and sensitisation to chemotherapeutic treatment. Genome-wide gene expression analysis and nucleoside and nucleotide profiling revealed that knockdown of ENPP1 affects purine and pyrimidine metabolism, suggesting a link between ENPP1 expression and a balanced nucleoside-nucleotide pool in GSCs. The phenotypic changes in E-NPP1-deficient GSCs are assumed to be a consequence of decreased transcriptional function of E2F1. Together, these results reveal that E-NPP1, by acting upstream of E2F1, is indispensable for the maintenance of GSCs in vitro and hence required to keep GSCs in an undifferentiated, proliferative state.